2015
DOI: 10.1111/1754-9485.12332
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the accuracy of the XVI dual registration tool compared with manual soft tissue matching to localise tumour volumes for post‐prostatectomy patients receiving radiotherapy

Abstract: XVI's DRT is comparable with RTs manually matching soft tissue on CBCT. The DRT can minimise RT inter-observer variability; however, involuntary bladder and rectal filling can influence the tools accuracy, highlighting the need for RT evaluation of the DRT match.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 12 publications
1
22
1
Order By: Relevance
“…A sliding scale is then used to find the best ‘compromise’ match between the two surrogates. Successful application of this software has been reported for patients receiving radiotherapy for lung cancer and regional lymph nodes, multiple lung metastases and for post‐prostatectomy surgical bed …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sliding scale is then used to find the best ‘compromise’ match between the two surrogates. Successful application of this software has been reported for patients receiving radiotherapy for lung cancer and regional lymph nodes, multiple lung metastases and for post‐prostatectomy surgical bed …”
Section: Discussionmentioning
confidence: 99%
“…Successful application of this software has been reported for patients receiving radiotherapy for lung cancer and regional lymph nodes, 36 multiple lung metastases 37 and for post-prostatectomy surgical bed. 38 In conclusion, for disease sites that require the concurrent irradiation of multiple, independently moving CTVs, there is a complex geometric interplay between the magnitude of CTV displacement differences, the PTV margins and the image guidance strategy applied. This study demonstrated the feasibility of a simple compromise position image guidance strategy to accommodate simultaneous displacements of two independently moving CTVs during pelvic radiotherapy for high risk prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographers found the multiple ROI easy to use with little additional workload and that it helped to identify patients for re-planning 12 . This software is not commercially available for routine clinical use; however, Elekta Dual Registration (DR) is available 14 . DR allows the registration of two separate regions of anatomy, calculating their positional offsets independently, and proposing joint correction that best fit both ROIs.…”
Section: Introductionmentioning
confidence: 99%
“…Manual corrections can be made to the proposed correction via applying a sliding-scale weighting to favour one ROI's over the other prior to applying the correction. Pre-set limits also alert the radiographer if a treatment target structure has moved closer to a critical structure 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation